Are petrous bones just a repository of ancient biomolecules? Investigating biosystematic signals in sheep petrous bones using 3D geometric morphometrics. (June 2022) - Bader, Camille; Mallet, Christophe; Chahoud, Jwana; Amane, Agraw; De Cupere, Bea; Berthon, Remi; Lavenne, Franck; Mohaseb, Azadeh; Davoudi, Hossein; Albesso, Moussab; Fathi, Homa; Vuillien, Manon; et al.
Highlights: Petrous bones are systematically destroyed for aDNA research. New methods based on 3D virtual morphology could help reduce destructive samplings. 3D geometric morphometrics of caprines' petrous bones provide encouraging results. Interspecific taxonomy are highly accurate and population history accessible. 3D geometric morphometrics survey could help targeting biomolecular studies. Abstract: Over the last decade, the petrous bone ( petrosum ) has become the ultimate repository of ancient biomolecules, leading to a plea for a more ethical curation preventing the systematic destruction of this bioarchaeological archive. Here, we propose to explore the biosystematic signal encompassed in the biological form of 152 petrosa from modern populations of wild and domestic sheep landraces/breeds across Western Europe, South-Western Asia and Africa, using high resolution geometric morphometrics (GMM) and the latest development in 3D virtual morphology. We assessed the taxonomic signals among wild and domestic caprine species and sheep landraces. We also explored the effect of sexual dimorphism and ageing at the population scale. Finally, we assessed the influence of climatic factors across the geographic distribution of our dataset using Köppen-Geiger climate categories. We found that the 3D form of petrous bones can accurately separate wild and domestic caprine taxa and that it is not influenced by sexual dimorphism, post-natal ageing or horn bearing. Recent selective breeding has not induced sufficient diversification to allow accurate identification of the different landraces/breeds in sheep; however, both genetic distance and climatic differences across the current distribution in sheep landraces/breeds strongly contribute to petrosum intraspecific variation. Finally, human mediated dispersal of domestic sheep outside their Near Eastern cradle, especially towards Africa, have greatly contributed to the diversification of sheep petrous bone form and shape. We therefore highly recommend systematic 3D surface modelling of archaeological petrosa with preliminary GMM studies to help target and reduce destructive biomolecular studies.